Peran Modal Sosial dalam Pengelolaan Badan Usaha Milik Desa Maju Bersama di Desa Sei Jawi-Jawi Kecamatan Sei Kepayang Barat Kabupaten Asahan - Zulpahmi Zulpahmi; Badaruddin Badaruddin; Humaizi Humaizi (Universitas Medan Area, 2020)
BUMDes Maju Bersama is a government program to help the economy of the people of Sei Jawi-jawi Village and achieve community welfare so that the Sei Jawi-jawi people get a decent living. This study aims to determine the role of social capital which is a driving force in the management of the Joint Forward BUMDes in Sei Jawi-jawi Village, Sei Kepayang Barat District, Asahan Regency. Social capital plays an important role in strengthening village communities. BUMDes can advance together with social capital. BUMDes Maju Bersama was established as an effort to increase the economic development of rural communities and create independence for the people in Sei Jawi-jawi Village. This research is a qualitative descriptive study. The location of the study was in Sei Jawi-jawi Village, Sei Kepayang Barat District, Asahan Regency. The object of this research is BUMDes Maju Bersama Sei Jawi-jawi Village. Data collection techniques using observation, interviews, and documentation. The results showed that the formation of BUMDes Maju Bersama was carried out in 3 (three) stages, namely the pre-village deliberations, village deliberations and post-village deliberations. So, this deliberation activity aims to determine what type of BUMDes will be formed in the hope that it will benefit the community. Social capital in the form of networks, norms and beliefs that play a role in the management of BUMDes Maju Bersama can be said to be not good enough even though BUMDes Maju Bersama is already operational and can contribute to the Village. This can be seen from the BUMDes Maju Bersama cooperation network that is still small, with collateral or collateral provided by BUMDes, the interest given by the management is too high, almost the same as the existing cooperatives and there is still public debt arrears. The informant's subjects from this study were the Village Head, Village Officials, BUMDes Maju Bersama Management, BUMDes Supervisor, parties who knew BUMDes and the Community who knew about BUMDes Maju Bersama.